THE IMPACT OF PROFITABILITY ON COMPANY VALUE WITH MEDIATION OF FINANCIAL DISTRESS IN CONVENTIONAL BANKING LISTED ON THE IDX 2020-2023 - Fiatun, Ida; Mardiana, Mardiana (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to examine if profitability impacts company value in conventional banking businesses listed on the IDX, the Indonesian Stock Exchange, during 2020-2023, using financial distress as a mediating variable. Using secondary data from the financial statements of 27 banks selected through purposive sampling techniques, this study adopts a quantitative methodology. Data analysis using path analysis with E-Views 12 software. Based on the study's results, financial distress significantly impacts company value, whereas profitability has no discernible impact. In addition, profitability significantly affects financial distress. However, the connection between company value and profitability cannot be mediated by financial distress. This study suggests that banks can manage financial distress effectively to increase firm value. Further research should consider other variables affecting firm value, such as macroeconomic conditions and stock market trends. Keywords: Firm Value; Profitability; Financial Distress